Defining Communication Problems in Stakeholder Relations Based on Stakeholder Theory - Helpris Estaswara (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2020)
Relationship with stakeholders has been widely seen as a communication phenomenon. Indeed, communication has long played an essential role in stakeholder theory. This study analyzed stakeholder relations in the communication discipline, which still left a room for review, based on stakeholder theory in the context of company management. Specifically, this study focused on both concepts in stakeholder relations, which was studied in communication science, and stakeholder theory, which was grounded on business ethics and strategic management. The concepts were analyzed using a social-oriented framework, and the aim was to disentangle and make evident the communication problems in this issue. The study used a literature review, to map the body of knowledge, and a qualitative approach based on a multi-disciplinary perspective. This study recommended that stakeholder relations be a communication discipline, and it should examine stakeholders based on two interrelated analyses, namely normative and strategic. Stakeholder relations should focus on normative-ethical studies, which were rooted in idealism. The strategic-operative aspects, which originated from realism, by contrast, could be delegated to other disciplines, such as public relations, organizational communication, corporate communication, strategic communication, to communication management.